2021
DOI: 10.37992/2021.1203.106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the performance, variability and nature of pearl millet productive traits in the rainfed environment of Andhra Pradesh

Abstract: An effort was made to examine one forty pearl millet hybrids in order to assess genetic variance and investigate the relationship between nine yield contributing traits. The study of variance showed that the crosses had significant genetic variability. An attempt was made to choose the best hybrids for grain yield and adaptation to low rainfall regions in arid Alfisols of Andhra Pradesh. Among the tested cross combinations, ABH-61, ABH-50 and ABH-77 were found to be promising for higher yield potential, emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The length of the panicle was found to be proportionate to the plant height. These findings agree with the results of Narasimhulu et al (2021b). Hence, the correlation matrix analysis conducted in this study identified several traits that were positively associated with grain yield in pearl millet.…”
Section: Association Analysissupporting
confidence: 92%
“…The length of the panicle was found to be proportionate to the plant height. These findings agree with the results of Narasimhulu et al (2021b). Hence, the correlation matrix analysis conducted in this study identified several traits that were positively associated with grain yield in pearl millet.…”
Section: Association Analysissupporting
confidence: 92%